Synthesis of some novel triazole derivatives as anti-nociceptive and anti-inflammatory agents - Rajasekaran, Aiyalu (Array, 2009)
Sintetizirano je osam novih 1-[2-(1H-tetrazol-5-il)etil]-1H-benzo[d][1,2,3]triazola (3a-h), s potencijalnim anti-nociceptivnim i protuupalnim djelovanjem